A review on hierarchical Bi2MoO6 nanostructures for photocatalysis applications. (14th December 2021) - Yin, Guoliang; Jia, Yulong; Lin, Yinhe; Zhang, Chenyang; Zhu, Zhenghai; Ma, Ying
Abstract : This overview provides comprehensive understanding and development trends of hierarchical Bi2 MoO6 nanostructures as photocatalysts for efficient photocatalysis applications. Abstract : In this critical review, hierarchical Bi2 MoO6 nanostructures as photocatalysts for photocatalytically degrading organic materials are summarised in detail. Hierarchical nanostructures have attracted much attention due to their multiple advantages such as a porous structure, large surface area, efficient light harvesting and charge separation, which have considerable influences on the photocatalytic performance. Herein, the recent progress of hierarchical Bi2 MoO6 nanostructures including primary, secondary and multiple structures is highlighted. Particularly, the morphologies, photocatalytic performance and mechanism of hierarchical Bi2 MoO6 nanostructures are outlined. Finally, further development prospects of Bi2 MoO6 photocatalysts are suggested. Hence, this systematic overview of hierarchical Bi2 MoO6 will offer guidelines for designing efficient photocatalysts for environmental applications.